2017
DOI: 10.1371/journal.pone.0186954
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus increases the susceptibility to encephalitozoonosis in mice

Abstract: Microsporidiosis are diseases caused by opportunistic intracellular fungi in immunosuppressed individuals, as well as in transplanted patients, the elderly and children, among others. Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycemia and decreased T cell response, neutrophil function, humoral immunity failure, increasing the susceptibility to infections. Here, we investigated the susceptibility of streptozotocin (STZ)-induced type I diabetic and/or immunosuppressed mice to encephalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
6
1
Order By: Relevance
“…The cytotoxic effect of this drug is due to the interaction of its alkylating metabolites with DNA. Treatment with Cy reportedly aggravated E. cuniculi infection, rendering it more severe, widespread, and with significantly increased lethality [10, 15, 16, 17]. Contrary to the observations related to the intravenous infection of mice with E. cuniculi [18], in the present study, the fungal load was lower in the immunosuppressed group compared to the mice not treated with cyclophosphamide and then infected with E. cuniculi , which is quite intriguing.…”
Section: Discussioncontrasting
confidence: 76%
“…The cytotoxic effect of this drug is due to the interaction of its alkylating metabolites with DNA. Treatment with Cy reportedly aggravated E. cuniculi infection, rendering it more severe, widespread, and with significantly increased lethality [10, 15, 16, 17]. Contrary to the observations related to the intravenous infection of mice with E. cuniculi [18], in the present study, the fungal load was lower in the immunosuppressed group compared to the mice not treated with cyclophosphamide and then infected with E. cuniculi , which is quite intriguing.…”
Section: Discussioncontrasting
confidence: 76%
“…In a previous study, we demonstrated that diabetes mellitus (DM) increased the susceptibility of C57BL/6 mice to encephalitozoonosis and DM mice infected with E . cuniculi showed higher levels of IL-6 than DM- uninfected mice, suggesting that DM may also modulate a pro-inflammatory state of the organism [49]. In the current study, we observed an increase in IL-6- in XID APerC after 1 h and 48 h of cultures infection, associated with an increase in the production of IL-10, a fact that suggests an anti-inflammatory effect of IL-6 corroborating the descriptions referring to its pleiotropic behavior, sometimes as a pro-inflammatory cytokine and sometimes as an anti-inflammatory cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…However, diabetes is considered a risk factor for opportunistic infections. Experimental infection of diabetic mice with E. cuniculi resulted in more symptoms and a higher pathogen burden than in nondiabetic animals ( 12 ); indeed, the woman with diabetes in our study experienced more severe symptoms, which led to serious impairments in everyday functioning.…”
Section: Discussionmentioning
confidence: 54%